ARIMA based forecasting of solar and hydro energy consumption with implications for grid stability and renewable policy - Chandra Prakash; Bijesh Dhyani; Anand chauhan; Anu Sayal (Discover Sustainability)
Abstract The global energy market is significant in establishing economic activities and policy decisions, and hence, Accurate forecasting of renewable energy consumption is critical for optimizing grid management and achieving decarbonization targets. This study develops a seasonal ARIMA (SARIMA) model to predict solar and hydro energy consumption across 140 countries (1965–2023), leveraging hyperparameter tuning (p, d, q) = (2, 1, 2) for solar and (1, 0, 1) for hydro energy. RMSE and R² scores are used to model evaluation metrics for validity of the predictions, our model achieves high accuracy (RMSE: 3.45 solar, 4.12 hydro; R²: 0.87 solar, 0.81 hydro) and reveals divergent trends: hydro consumption remains stable, while solar adoption fluctuates with policy and market shifts. The results provide actionable insights for energy planners to mitigate intermittency challenges and align infrastructure investments with regional renewable potential.